Alterations of Ultra Long-Chain Fatty Acids in Hereditary Skin Diseases—Review Article - Zwara, Agata; Wertheim-Tysarowska, Katarzyna; Mika, Adriana (Frontiers in Medicine, 2021)
The skin is a flexible organ that forms a barrier between the environment and the body's interior; it is involved in the immune response, in protection and regulation, and is a dynamic environment in which skin lipids play an important role in maintaining homeostasis. The different layers of the skin differ in both the composition and amount of lipids. The epidermis displays the best characteristics in this respect. The main lipids in this layer are cholesterol, fatty acids (FAs) and ceramides. FAs can occur in free form and as components of complex molecules. The most poorly characterized FAs are very long-chain fatty acids (VLCFAs) and ultra long-chain fatty acids (ULCFAs). VLCFAs and ULCFAs are among the main components of ceramides and are part of the free fatty acid (FFA) fraction. They are most abundant in the brain, liver, kidneys, and skin. VLCFAs and ULCFAs are responsible for the rigidity and impermeability of membranes, forming the mechanically and chemically strong outer layer of cell membranes. Any changes in the composition and length of the carbon chains of FAs result in a change in their melting point and therefore a change in membrane permeability. One of the factors causing a decrease in the amount of VLCFAs and ULCFAs is an improper diet. Another much more important factor is mutations in the genes which code proteins involved in the metabolism of VLCFAs and ULCFAs—regarding their elongation, their attachment to ceramides and their transformation. These mutations have their clinical consequences in the form of inborn errors in metabolism and neurodegenerative disorders, among others. Some of them are accompanied by skin symptoms such as ichthyosis and ichthyosiform erythroderma. In the following review, the structure of the skin is briefly characterized and the most important lipid components of the skin are presented. The focus is also on providing an overview of selected proteins involved in the metabolism of VLCFAs and ULCFAs in the skin.